2020
DOI: 10.1038/s41598-020-70897-z
|View full text |Cite
|
Sign up to set email alerts
|

Implications of back-and-forth motion and powerful propulsion for spirochetal invasion

Abstract: the spirochete Leptospira spp. can move in liquid and on a solid surface using two periplasmic flagella (pfs), and its motility is an essential virulence factor for the pathogenic species. Mammals are infected with the spirochete through the wounded dermis, which implies the importance of behaviors on the boundary with such viscoelastic milieu; however, the leptospiral pathogenicity involving motility remains unclear. We used a glass chamber containing a gel area adjoining the leptospiral suspension to resembl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…The enhancement of the motion-mode switching is observed in Ficoll, methylcellulose, and mucin solutions [16]. In addition, we revealed that the swimming direction reverses more frequently in high viscosity (Figure 2a) [16,20]. Enhancing "back and forth" movement suggests the limitation of the net migration, crowding bacteria within the mucus layer, and facilitating colonization over the tissues (Figure 2b).…”
Section: Back-and-forth Motionmentioning
confidence: 80%
See 2 more Smart Citations
“…The enhancement of the motion-mode switching is observed in Ficoll, methylcellulose, and mucin solutions [16]. In addition, we revealed that the swimming direction reverses more frequently in high viscosity (Figure 2a) [16,20]. Enhancing "back and forth" movement suggests the limitation of the net migration, crowding bacteria within the mucus layer, and facilitating colonization over the tissues (Figure 2b).…”
Section: Back-and-forth Motionmentioning
confidence: 80%
“…Leptospira switches swimming direction within <1 s [20]. Such a quick reversal suggests the coordination between two PFs mediated by unidentified signal transduction, but there is no definitive evidence so far.…”
Section: Interaction Between Pfsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, we could not rule out the role of other Rho regulatory proteins such as p120‐catenin which is altered in L. interrogans ‐ infected RPTECs (Schackmann, Tenhagen, van de Ven, & Derksen, 2013 ) (Figure 8 ). Moreover, the tight interactions of L. interrogans with the plasma membrane and efficient propulsion of L. interrogans using back ‐and forth movements can facilitate their invasion through AJCs and apply an additional mechanical force to enhance AJC disassembly (Abe, Kuribayashi, Takabe, & Nakamura, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Leptospires are unique in that they have a single supercoiled endoflagellum extending axially toward the middle of the cell from a flagellar motor embedded in the inner membrane at each pole, without overlap. Endoflagellar rotation imparts a swimming motility that enables leptospires to be particularly invasive at liquid–gel borders, such as the interface between the vascular lumen and the endothelium, with 30 times the swimming force of Escherichia coli [ 16 ]. Recent elegant high-resolution cryo-electronic tomography studies have shown that the function of leptospiral endoflagellar filaments relies on an asymmetric sheath that imparts their supercoiled structure [ 17 ].…”
Section: Introductionmentioning
confidence: 99%